Phytochemical profile and anti-inflammatory effect of Artemisia annua L. essential oil - Congcong Zhu; Ge Yan; Manqi Hu; Zongguang Tai; Bin Fan; Pei Zhao; Xiao Miao; Quangang Zhu (All Life, 2023)
Plant-derived natural compounds are desired for their anti-inflammatory properties. We investigated the chemical composition and the anti-inflammatory effects of the essential oil obtained from leaves of the Chinese medicinal plant Artemisia annua L. Artemisia annua L. essential oil (AO) was obtained by hydrodistillation; the extraction yield was approximately 1.2%. Gas chromatography–mass spectrometry (GC–MS) revealed the presence of 13 compounds in AO; the major compounds were caryophyllene (32.16%), eucalyptol (28.62%), α-pinene (19.08%), and β-pinene (14.72%). Cell counting kit-8 (CCK8) assay revealed that AO did not show in vitro cytotoxicity toward RAW264.7 cells and suppressed the expression of nitric oxide (NO), tumor necrosis factor-alpha (TNF-α), and interleukin-6 (IL-6) in lipopolysaccharide (LPS)-induced RAW264.7 cells. Pretreatment with AO significantly reduced xylene-induced inflammation in the ears of Kunming mice. AO inhibited inflammatory cell infiltration, decreased epidermis thickness in the ear, and suppressed expression of TNF-α in the serum. The in vivo anti-inflammatory activity of AO was similar to that of the positive control compound Di Song Zhang Bo Cream. Overall, AO was observed to be an effective anti-inflammatory agent. These results provide an experimental basis for commercializing AO-derived external preparations for pharmacological and cosmetic industries.